Ideals versus Dollars: Donors, Charity Managers, and Government Grants - Rose-Ackerman, Susan (Journal of Political Economy, 1987)
This paper demonstrates how changes in untied, lump-sum government grants or income from unrestricted endowments will affect the behavior of charities operated by managers with s trong philosophical or professional commitments. An increase in such funds will reduce the charity's accountability to private donors and lower its fund-raising activities. The grant will not be spent entire ly on raising the quantity of output. Instead, it will permit the cha rity manager to reduce his or her dependence on the costly solicitati on of donors who do not completely share the manager's preferences. Copyright 1987 by University of Chicago Press.